Measurement of blood loss during postpartum haemorrhage. Issue 1 (February 2015) - Lilley, G.; Burkett-st-Laurent, D.; Precious, E.; Bruynseels, D.; Kaye, A.; Sanders, J.; Alikhan, R.; Collins, P.W.; Hall, J.E.; Collis, R.E.
Highlights We evaluated gravimetric measurement of blood loss at postpartum haemorrhage. We compared measured blood loss with fall in haemoglobin after postpartum haemorrhage. We used simulation to compare gravimetric measurement with visual estimation. A good correlation exists between gravimetrically measured blood loss and fall in haemoglobin. Gravimetric measurement was more accurate than visual estimation in simulated postpartum haemorrhage.